High fetal splenic artery peak velocity in fetuses with hemoglobin Bart disease: A preliminary study - Theera Tongsong (2018)
Objective. The purpose of this study was to evaluate the role of the splenic artery (SPA) peak systolic velocity (PSV) in identifying fetuses with hemoglobin (Hb) Bart disease among pregnancies at risk for the disease. Methods. Pregnancies at risk for fetal Hb Bart disease scheduled for cordocentesis at 18 to 25 weeks' gestation at Maharaj Nakorn Chiang Mai Hospital were recruited into the study. The SPA PSV was measured before cordocentesis, and the final fetal diagnosis of Hb Bart disease was based on fetal Hb typing using high-performance liquid chromatography. Results. Seventy-six singleton pregnancies at risk for fetal Hb Bart disease were sonographically evaluated for the SPA PSV and underwent cordocentesis for fetal blood analysis. Among the 76 recruited pregnancies, 17 fetuses with Hb Bart disease were finally diagnosed by fetal blood analysis with high-performance liquid chromatography, and the remainder had no abnormalities or had the α-thalassemia 1 trait and were defined as unaffected fetuses. The mean SPA PSVs ± SD for the unaffected and affected fetuses were significantly different: 21.17 ± 3.7 cm/s (range, 13.8-29.9 cm/s) and 26.12 ± 3.6 cm/s (range, 20.4-31.5 cm/s) respectively. The SPA PSV of the affected fetuses was higher than that of the unaffected ones (Wilcoxon signed rank test, P < .001). Conclusions. Splenic artery PSV assessment at mid pregnancy may have a potential role in identifying fetuses with Hb Bart disease. Further studies to evaluate the effectiveness of the SPA PSV in differentiating affected from unaffected fetuses among pregnancies at risk are desirable. © 2009 by the American Institute of Ultrasound in Medicine.